Edukasi Pengelolaan Sampah Rumah Tangga pada Warga Sekitar Lokasi Bank Sampah Emo-G Kabupaten Bogor - Sulistiyorini, Desy; Demiyati, Cici (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Garbage is now one of the biggest problems in Indonesia. Indonesia produces 64 million tons of garbage annually, most of which is household waste. If not properly managed, waste can block waterways, resulting in environmental pollution and health impacts. The method of community service activities is educational management of household garbage around the location of Emo-G Waste Bank Bogor district. The event was attended by 20 participants who were present and given a questionnaire at the beginning and end. The analysis results showed an increase in the average knowledge score of respondents related to garbage management, with an average pre-test score of 8,17 and a post-test average of 8,25. For the variable attitude towards garbage management, there was also an increase in the average score, where the pre-test score was 8,33, and the post-sitting score was 8,67. An increase was observed for the waste management behavior variable, with an average pre-test score of 7,42 and an average post-test score of 8,08. Based on the results of the internal evaluation, the team's service to the community is rated as running fairly well. Recommendations to citizens are expected to participate more actively in household garbage disposal activities and to deposit in the trash bank to reduce the waste burden that the TPA has to manage and also bring economic benefits for citizens as the saved trash can be converted into monetary value.